Bengkel Sat-Set: Solusi Digital untuk Membantu Dalam Melakukan Reservasi Perbaikan Kendaraan via Aplikasi Android - Herman; Fariwati; Triyanti, Vivie; Lia Febrianti, Eka (Fakultas Komputer - Universitas Universal, 2025)
This research presents a design of software requirements specifications for Bengkel Sat-Set, an Android-based mobile application designed to simplify the digital ordering and management of vehicle service. This application is designed as a solution to various problems often encountered in conventional repair shop systems, such as long queues, lack of transparency regarding repair status, and limited access to vehicle service history. With this application, users are expected to be able to order services online, monitor vehicle repair status in real-time, and view service history without having to visit the repair shop in person. This system design uses a software engineering approach, with technical specifications using the Kotlin programming language for developing the Android interface and Firebase as the backend service. Firebase was chosen for its ability to provide efficient and secure data storage, user authentication, and real-time data communication. This research focuses on the early stages of development, namely designing the system's functional and non-functional requirements, including user flows and initial architecture. The primary objective of this paper is to provide a conceptual and technical foundation as part of the digital transformation process in the automotive service sector. It is hoped that through the design of this Sat-Set Workshop application, workshop service providers can improve operational efficiency, expand service access, and increase customer satisfaction through the use of adaptive and user-friendly digital technology.